How does perceived ease of information access affect investors' judgments? - Cikurel, Deni (Contemporary Accounting Research, 2024)
Abstract This study investigates how using technologies that increase the perceived ease of information access, such as search engines, can affect investors' judgments. Relying on the “Google effect” theory, I predict that using a search engine to access financial information will lead to shallower processing of that information, causing earnings fixation. The results of three experiments support this prediction and the theoretical process. Specifically, investors who access financials via a search engine are less likely to react to the information in the income statement other than earnings compared to those who do not use a search engine. In addition, search condition investors are more likely to mention earnings in their investment reasoning and find earnings more influential than the control condition investors. Furthermore, search condition investors believe that information is more likely to be available in the future and are more likely to reopen the income statement. A second experiment shows that the knowledge that the information will be easily reaccessed increases investors' earnings fixation. Finally, a third experiment provides evidence that using a search engine reduces the depth of information processing. This study extends accounting research by showing that using technologies that increase the perceived ease of information access can reduce investors' processing depth and information acquisition.